Optimización de la gestión de la información en el área de perforación y completamiento de Ecopetrol S.A. mediante la herramienta "Datamart" (2020)
To carry out the optimization of information management in the area of drilling and completion of Ecopetrol S.A. 111 oil wells from 11 fields corresponding to the Regional Vice Presidency Orinoquía de Ecopetrol S.A. were analyzed. In order to achieve this objective, it began with a description and verification of the databases managed by management, identifying requirements and essential indicators for each event of the operation. For example, number of wells drilled, total feet drilled, total cost per foot drilled, and in order to determine what are the problems faced by staff when preparing reports and / or making decisions. After this, we proceeded to explain in a technical way the generalities of the proposed tool (Datamart), and implement the necessary information for the data processing. Finally, the results were evaluated and the tool implementation plan that optimized the time required for the search, processing and deployment of information necessary for decision making was proposed.